PELAKSANAAN PROSES PEMBELAJARAN TATAP MUKA PROGRAM PENDIDIKAN KESETARAAN PAKET B DIPKBM AL’ILMI RIAU KOTA PEKANBARU - Widya Marta Yanti; Wilson Wilson; Jaspar Jas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The formulation of the problem in this research is How the Implementation of Face-to-Face Learning Process of Package B Equality Education Program in PKBM Al'Ilmi Riau Kota Pekanbaru. The purpose of this study was to determine the implementation of face-to-face learning process of equivalence education program B in PKBM Al'Ilmi Riau Kota Pekanbaru. This study uses a descriptive study with a qualitative approach that aims to provide a systematic description of the ongoing situation in the object of research, namely the implementation of face-to-face learning process package E equality education program in PKBM Al'Ilmi Riau Kota Pekanbaru. Informants in this study were 4 informants consisting of 2 core informants, 1 control informant, and 1 supporting informant. The research instrument used was the interview guide grid, which was to obtain data on the implementation of face-to-face learning process of package B equality education program at PKBM Al 'Ilmi Riau, Kota Pekanbaru. Data obtained through documentation, observation and interviews. Then analyzed using triangulation.Key Words: Implementation, Face to Face Learning, Package Program B